Abundance of Road Traffic Accidents among Medicolegal Postmortem Cases - Rahman, MZ; Ahmad, M; Rahman, FN; Islam, SMK; Rahman, KGM; Haque, MR (Faridpur Medical College Journal, 2011)
This retrospective study was conducted at the Dhaka Medical College (DMC) morgue during the period of Jan 2008 to Dec 2008. The objective of this study was to find out the abundance of Road Traffic Accidents (RTA) cases among medicolegal post mortem examinations performed at DMC morgue and in this relation to evaluate the present situation of RTA in our country. It has been observed that RTA cases are the most common cases among various types of medicolegal post mortems. A total of 2714 postmortems were conducted during the study period and out of which 813 (29.95%) cases were of RTA, among the victims 545 (67.03%) were male and 268 (32.96%) were female. Highest incidence (30.38 %) of RTA was observed among the age group 21 to 30 yrs. Most accidents occurred at daytime 282 (34.68%), followed by night 233 (28.66%). Greater number of accidents occurred during September 90 (11.07%), followed by January 85 (10.45%) and December 83 (10.20%). Commonest victims were pedestrians 564 (69.37%). Most accidents took place on highways 650 (79.95%) and buses were the most dangerous vehicle causing highest number of accidents 307 (37.76%), followed by truck 141 (17.34%). Among the cases 100% victims had multiple abrasion and bruise, laceration were present in 654 (80.44%), and intra cranial injury 527 (64.82 %). Key words: Road Traffic Accidents; Postmortem Examination DOI: 10.3329/fmcj.v6i1.7407 Faridpur Med. Coll. J. 2011;6(1): 28-31